2021
DOI: 10.14202/vetworld.2021.854-859
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of long-term survival of African swine fever virus in natural conditions

Abstract: Background and Aim: In modern scientific literature presents an understanding that African swine fever (ASF) ASF virus (ASFV) is remarkably stable in the environment, and carcasses of the pigs which were died after ASF, play a key role as ASFV reservoir. The aim of this study was to evaluate the possibility of the ASFV (different isolates) survival in bodies of dead animals, bones, remnants of bone marrow, residual organ matrix in natural conditions. Materials and Methods: Skeletons of ASFV infected pigs whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…Studies on food habits of wolves indicate that wild boar is their main prey, reaching up to 50% of wolves' diet [47,48]. All experts indicated that predation occurred mainly on piglets or juveniles, being more frequently in spring, although they can also predate during the whole year, as 48% of experts agreed and in line with other studies [43,44]. Two new concerns expressed by experts were the possibility of wild boar increasing movements and range, leading to ASF dispersal because of wolf activities, and the potential overlapping of wolves and other potential predators with wild boar in natural and agroforestry areas.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Studies on food habits of wolves indicate that wild boar is their main prey, reaching up to 50% of wolves' diet [47,48]. All experts indicated that predation occurred mainly on piglets or juveniles, being more frequently in spring, although they can also predate during the whole year, as 48% of experts agreed and in line with other studies [43,44]. Two new concerns expressed by experts were the possibility of wild boar increasing movements and range, leading to ASF dispersal because of wolf activities, and the potential overlapping of wolves and other potential predators with wild boar in natural and agroforestry areas.…”
Section: Discussionsupporting
confidence: 80%
“…On one hand, scavengers reduce the time a carcass remains in the environment, decreasing environmental persistence, but on the other hand, not all carcass remains are removed, and bones in particular will remain [17,43]. ASF virus genome can remain preserved in bones and the remnants of bone marrow of buried carcasses for more than two years [44]. Furthermore, some mammals and birds can transport pieces of meat in their mouths or beaks, contributing to local ASF spread [43].…”
Section: Discussionmentioning
confidence: 99%
“…Another highly important characteristic in terms of virus survival is the stability of the virus against proteases and nucleases [1]. The cause of the high resistance of viral particles lies in the extremely complex structure of the virion [10]. ASFV is the sole member of the Asfarviridae family and belongs to the group of large nucleocytoplasmic DNA viruses.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ASFV can remain viable in natural conditions for long time periods ( Arzumanyan et al, 2021 ) and be directly transmitted by complex transmission routes such as contact between infected and susceptible pigs ( Gaudreault et al, 2020 ), consumption of infected pig meat ( Ito et al, 2020 ), and bites from infected acari ( Ornithodoros spp. ; Pereira De Oliveira et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%